An analyze Relevancy of Intern English Teacher’s Lesson Plan in Senior High School Of Malang - Chyntia Yolandari (Jetlal, 2022)
"For teachers, plan gives the lesson a framework, an overall shape," according to Harmer (2007, p.156). It refers to a lesson plan that instructs teachers on how to deliver teaching-learning activities. Teachers' ability to create lessons is critical for developing a strategy to increase the quality of teaching and learning activities. In order to achieve the National Education goals, lesson plans must be relevant to government regulations. The Indonesian government enacted Permendikbud No. 22 Tahun 2016 to control the Standar Proses. To assist instructors in creating lesson plans, the rule lists components of a lesson plan based on the 2013 curriculum. Especially for intern English teacher in order to designing lesson plan. The results of the document analysis revealed that all lesson plans included every component of a lesson plan, such as indicators and basic competences, objectives, materials, media, activities, and assessment; however, when the quality of each component was assessed using Permendikbud Nomor 22 Tahun 2016, the quality of each component varied. The findings of the study revealed that while intern English teachers' lesson plans were totally based on the 2013 curriculum, some components of the lesson plan were not applicable.